1992
DOI: 10.1200/jco.1992.10.1.102
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of high-dose cyclophosphamide, thiotepa, and carboplatin with autologous marrow support in women with measurable advanced breast cancer responding to standard-dose therapy.

Abstract: CTCb is an intensification regimen with a low mortality that delivers a significantly increased dose of agents with known activity at conventional doses in breast cancer. Although the duration of PR is short as expected, CRs appear to be durable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
131
2

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(137 citation statements)
references
References 29 publications
4
131
2
Order By: Relevance
“…The objective of this analysis was to describe the early and late toxicities of this regimen, which is similar to but not identical with the CTCb (STAMP-V) regimen described by Antman et al (1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The objective of this analysis was to describe the early and late toxicities of this regimen, which is similar to but not identical with the CTCb (STAMP-V) regimen described by Antman et al (1992).…”
Section: Discussionmentioning
confidence: 99%
“…The two studies (Peters et al, 1993;Nikcevich et al, 2002) that employed this carmustine-based combination reported high toxic death rates due to organ toxicity, mainly interstitial pneumonitis. Even very experienced centres that optimally exploit corticosteroids at the earliest sign of pulmonary symptoms report a 5% toxic death rate (Antman et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients (n = 9 in both arms) showed a TRF length decrease at t 1 , but also remarkable TRF length increases were observed; no significant decrease due to either treatment was found in paired samples. The high-dose treatment scheme used in this study is classically combined with stem cell support in view of its profound myolotoxicity, causing prolonged life threatening marrow aplasia (Ayash et al, 1993;Antman et al, 1994). It is possible that in individual patients the lack of TRF length decrease due to treatment may be interpreted as a sign of insufficient treatment toxicity, as stem cells remaining in the patient after high-dose treatment will have an impact on the requirements to divide for haematopoietic reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…When given as adjuvant treatment for high-risk stage II -III breast cancer (six patients), HDCT consisted of cyclophosphamide, tiothepa, and carboplatin (CTCb) as previously described (Antman et al, 1992). An antracycline-containing regimen (fluorouracil, epirubicin and cyclophosphamide) (FEC-75) had been given as induction prior to HDCT.…”
mentioning
confidence: 99%